Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```        cot x. cot 2x - cot 2x. cot3x - cot x. cot3x = 1

I am unable to get the LHS equal to RHS```
7 years ago

Tapasranjan Das
19 Points
```										Hi CHINMAYI,
L.H.S=cot x. cot 2x - cot 2x. cot3x - cot x. cot3x
=cot x. cot 2x - cot3x(cot 2x +cot x)
=cotx .cot 2x - cot (x+2x) .(cot 2x+ cot x)                       [we can write cot3x as cot(x+2x)]
=cotx.cot2x- {(cot x. cot 2x -1)/(cot x + cot 2x)}.(cot x + cot 2x)            [since cot(a+b)=(cot a. cot b -1)/(cot b+cot a)]
=cot x. cot 2x -cot x. cot 2x +1
=1
=R.H.S
```
7 years ago
Umang
11 Points
```										cot (3x) = cot ( 2x+x )Apply, cot (A+B) = (cot A.cot B -1)/ cot A + cot BSo,cot (3x) = ( cot 2x.cot x - 1 ) / cot 2x + cot xNow, cross multiplycot 3x ( cot 2x + cot x ) = cot 2x.cot x - 1cot 2x.cot 3x + cot x.cot 3x = cot 2x.cot x - 1cot 2x.cot x - cot 2x.cot 3x - cot x.cot 3x = 1
```
7 months ago
Think You Can Provide A Better Answer ?

Other Related Questions on Trigonometry

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details